Accuracy and mechanical performance of passivated and conventional fabricated 3-unit fixed dental prosthesis on multi-unit abutments. Issue 4 (October 2017) - Stimmelmayr, Michael; Groesser, Julian; Beuer, Florian; Erdelt, Kurt; Krennmair, Gerald; Sachs, Caroline; Edelhoff, Daniel; Güth, Jan-Frederik
Abstract: Purpose: The aim of this study was to evaluate the fit and mechanical stability of conventional versus passive fitting 3-unit fixed dental prosthesis (FDP) screw-retained on implants. Methods: Twenty acrylic models, each with two embedded implants, were fabricated and functioned as patient-models. Impressions were taken and 20 all-ceramic FDPs were pre-fabricated on the plaster casts. Respectively 10 FDPs were fixed on the plaster casts (group 1) and on the patient-models for passive fitting (group 2). The fit of each FDP was checked on the patient-model by means of visual control (grades 1–10) and microscopic examination. Furthermore, specimens were artificially aged for possible prosthodontic failures, followed by a fracture strength test. Results: Group 2 [1.4 (±0.3)] showed significantly (p < 0.001) better results in the visual examination of the marginal fit compared to group 1 [6.3 (±2.4)]. The microscopic marginal misfit was 160 μm (±80 μm) at the abutment margin and 150 μm (±80 μm) at the axial wall of the abutment for group 1, respectively, 0 μm and 0 μm up to 17 μm for group 2 (p < 0.001). No failure of the FDPs could be observed during artificial aging in both groups. The fracture load showed no significant difference (p = 0.60) between group 1 [2583 N (±664 N)] and group 2 [2465 N (±238 N)]. Conclusions: Visual and microscopic examination detected huge differences in marginal fit between groups 1 and 2. However, no statistically verifiable differences could be detected in long-term stability of implant-supported FDPs irrespective of the fit.